ANALISIS FAKTOR - FAKTOR YANG BERPENGARUH TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAPAT PADA BURSA EFEK INDONESIA - Singgih Adhi Julian, 09.05.52.0161; Wardjono, Wardjono (Students Journal of Accounting and Banking, 2016)
This study aims to determine Analysis of Factors Influencing Against Corporate Values In Manufacturing Companies Listed On Stock Efek Indonesia. Population in this research are manufacturing companies listed in Indonesia Stock Exchange 2012-2013. The sample in this study were taken by purposive sampling method. Data were analyzed using Independent sample t test. At variables debt policy statistically not significant effect on PBV, on variables asset growth is statistically not significant effect on PBV, on ROE statistically significant effect on PBV, at variable ASSET statistically not significant effect on PBV, the variable EPS statistically significant effect on PBV.Keywords: Debt Policy, Asset Growth, ROE, Asset, EPS, PBV